A Structural Equation Model on the Capabilities of the Bureau of Fire Protection in Emergency Response in Relation to Job Satisfaction, Motivation, and Training - Edon, Aiza; Nabe, Nestor (Journal of Interdisciplinary Perspectives, 2025)
This study developed a structural equation model to examine the capabilities of the Bureau of Fire Protection (BFP) in emergency response, focusing on job satisfaction, motivation, and training among 400 BFP personnel in Region 12. Employing a non-experimental quantitative approach using a descriptive-correlational design, the study utilized weighted means, Pearson's r, linear regression, and structural equation modeling for data analysis. Results revealed that BFP personnel in the region possess a very high level of emergency response capability, covering both firefighting and emergency medical services. Similarly, very high levels of job satisfaction, motivation, and training adequacy were reported. Significant positive correlations were established between emergency response capabilities and the three factors, with motivation emerging as the strongest predictor in the best-fit model (Model 3). These findings have practical implications for organizational development, underscoring the importance of prioritizing personnel motivation as a strategic lever to enhance emergency response effectiveness. Additionally, the results support theoretical frameworks that posit motivation and job satisfaction as critical drivers of performance in high-stakes service sectors. The study contributes to a more nuanced understanding of how internal organizational factors dynamically interact to influence frontline emergency capabilities, offering a data-driven basis for training and human resource interventions in the public safety sector.